The death of philosophy through the naturalization of the mind - Mabaquiao, Napoleon M., Jr. (Animo Repository, 2014)
In this essay, I try to make sense of the idea that philosophy will someday come to an end or "die." I first clarify how I understand such an idea, after which I present a viable hypothesis on what will bring it about. Accordingly, the "death of philosophy," to my mind, refers to an event in which that act of philosophizing is either no longer done or no longer taken to be worth doing. And given that a philosophical problem ceases to be philosophical one a scientific way to handle it has been established, I advance the hypothesis that philosophy's demise will come about once the project to naturalize the mind (or to explain its workings in purely scientific terms) is successfully completed. Three things make this hypothesis viable: (1) the centrality of the mind in philosophizing; (2) the power of the computational framework used to carry out this project; and (3) the seriousness with which this project is currently being pursued especially in the areas of (analytic) philosophy, cognitive science, and artificial intelligence.